Alleviated Double ITCZ Problem in the NCAR CESM1: A New Cloud Scheme and the Working Mechanisms. (22nd September 2018) - Qin, Yi; Lin, Yanluan
Abstract: Simulation of tropical precipitation in global climate models remains a challenge, in which double Intertropical Convergence Zone (ITCZ) bias is a prominent manifest. Compared with the original cloud scheme, a new diagnostic statistical cloud macrophysics scheme alleviates the spurious southern ITCZ bias associated with warm sea surface temperature (SST) bias over the central Pacific in the National Center for Atmospheric Research (NCAR) Community Earth System Model, version 1 (CESM1). Owing to the reduced net surface shortwave radiation associated with the increased low cloud fraction and liquid water path over the southeastern Pacific Ocean, the new scheme reduced local SST and further suppressed convection and precipitation. Stronger Walker circulation and enhanced tropical easterlies lead to increased tropical ocean zonal currents, which further lead to reduced SST in the central Pacific due to increased oceanic cold advection. As a result, over the central Pacific, SST cooling suppresses precipitation and alleviates the double ITCZ bias. The study suggests that low clouds over subtropical eastern ocean regions can impact tropical circulation and precipitation via a strong coupling with SST and ocean dynamics. Key Points: A diagnostic Gauss‐PDF cloud scheme improved subtropical low clouds in CESM simulations The double ITCZ bias is alleviated using the new scheme because of better simulated subtropical low clouds The working mechanisms root in the close air‐sea interaction among SST, tropical circulation, and oceanic heat transport